Distinct metabolic features of genetic liability to type 2 diabetes and coronary artery disease: a reverse Mendelian randomization study - Madeleine L. Smith; Caroline J. Bull; Michael V. Holmes; George Davey Smith; Eleanor Sanderson; Emma L. Anderson; Joshua A. Bell (2023)
Type 2 diabetes (T2D) and coronary artery disease (CAD) both have known genetic determinants, but the mechanisms through which their associated genetic variants lead to disease onset remain poorly understood.